Measuring Globalization of Industries Using a National Industry Approach: Empirical Evidence Across Five Countries and over Time - Makhija, Mona V.; Kim, Kwangsoo; Williamson, Sandra D. (Journal of International Business Studies, 1997)
This paper presents an objective measurement of industry globalization. Although crucial in understanding firm strategies, industry globalization has been largely subjectively measured, consisting of mostly case studies. This research develops a two-pronged measure of industry globalization based on (a) the extent of an industry's international linkages (LIT) and (b) the integration of value-added activities within the industry (IIT). In addition of providing a quantitative equivalent to Porter [1986] and Bartlett and Ghoshal's [1989] conceptual industry categorizations, this measure permits the examination of important but previously untested notions regarding globalization. Using data for chemical and manufacturing industries for five major trading nations, we find that (1) chemical industries are less global than manufacturing industries, despite high levels of FDI found in chemical industries; (2) U.S. globalization, frequently assumed to be representative of worldwide globalization of industries, is less than that of other major industrial countries; and (3) industries in both sectors are globalizing over time, consistent with the literature.